Design, Synthesis and Biological Evaluation of a Series of Thioamides as Non-Nucleoside Reverse Transcriptase Inhibitors - Mehanna, Ahmed S.; Belani, Jitendra D.; Kelley, Charles J.; Pallansch, Luke A. (Medicinal Chemistry, 2007)
A series of thioamides were designed as bio-isosteres to the non-nucleoside reverse transcriptase inhibitor trovirdine by replacement of the thiourea NH groups with methylene groups. Eight thioamides were synthesized and in vitro tested for inhibitory effects on the activity of HIV-1 reverse transcriptase wild and mutant types. Three of the 8- thioamides exhibited enzyme inhibitory activities with IC50 values below 100 μM. While compound (2) exhibited activity against the mutant strain L100I with IC50 of 70.1 μM, compound (4) showed activity against the mutant strain K103N with IC50 of 92.7 μM, and compound (8) with activity against the wild type enzyme with IC50 of 8.9 μM. Each of the three thioamides could serve as a lead compound for further activity optimization.
Keywords: thioamides